2009
DOI: 10.1051/0004-6361/200811430
|View full text |Cite
|
Sign up to set email alerts
|

Long-term asymmetry in the wings of the butterfly diagram

Abstract: Aims. Sunspot distribution in the northern and southern solar hemispheres exibit striking synchronous behaviour on the scale of a Schwabe cycle. However, sometimes the bilateral symmetry of the Butterfly diagram relative to the solar equatorial plane breaks down. The investigation of this phenomenon is important to explaining the almost-periodic behaviour of solar cycles. Methods. We use cross-recurrence plots for the study of the time-varying phase asymmetry of the northern and southern hemisphere and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 26 publications
5
60
0
1
Order By: Relevance
“…One may also wish to check its validity of some research on the latitudinal migration of solar activity. For example, some researchers have reported that latitudinal migration of sunspots asynchronously occur in the northern and southern hemispheres (Waldmeier 1971, Swinson et al 1986, Zolotova & Ponyavin 2006, Donner & Thiel 2007, Zolotova et al 2009, Li et al 2009a, b, 2010. They have attempted to explain the solar North-South asymmetry with such a phase difference between paired wings of the butterfly diagram instead of appreciating the real asymmetry in two hemispheres.…”
Section: Center-of-latitude Of Sunspotmentioning
confidence: 99%
“…One may also wish to check its validity of some research on the latitudinal migration of solar activity. For example, some researchers have reported that latitudinal migration of sunspots asynchronously occur in the northern and southern hemispheres (Waldmeier 1971, Swinson et al 1986, Zolotova & Ponyavin 2006, Donner & Thiel 2007, Zolotova et al 2009, Li et al 2009a, b, 2010. They have attempted to explain the solar North-South asymmetry with such a phase difference between paired wings of the butterfly diagram instead of appreciating the real asymmetry in two hemispheres.…”
Section: Center-of-latitude Of Sunspotmentioning
confidence: 99%
“…While some aspects of the underlying nonlinear dynamics have been revealed in the past using a variety of different analysis techniques, there are a multitude of observed phenomena that have not yet been fully understood. One of these findings is on the hemispheric asymmetry of solar activity, which manifests itself in the statistical properties of a variety of activity indicators such as sunspot numbers, areas and spatial distribution, the numbers of flares and coronal mass ejections, solar radio and Xray flux, and has been recognized to vary on multi-decadal timescales (see, e.g., Newton and Milsom, 1955;Carbonell et al, 1993;Zolotova and Ponyavin, 2006;Donner and Thiel, 2007;Donner, 2008;Li et al, 2008;Li, 2008;Zolotova et al, 2009, and references therein). Notably, it is commonly believed that the observed distinct hemispheric asymmetry is an intrinsic property associated with underlying solar magnetic field dynamics, which in turn serves as the driver of solar activity responsible for particle and electromagnetic emissions directly affecting the Earth.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been argued that phase information should be explicitly taken into account as well, noting that a mutual time shift between the activity cycles observed separately at both solar hemispheres could provide a significant contribution to the observed asymmetry (Zolotova and Ponyavin, 2006;Donner and Thiel, 2007). As a particularly powerful tool, an extraction of the main variability components related to the approximately 11-year Schwabe cycle by means of continuous wavelet transform has been found to be widely applied (Donner and Thiel, 2007;Donner, 2008;Li et al, 2008Li et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…However, solar activity is found to be sightly asynchronous between the northern and southern hemispheres from recent studies (Ponyavin & Zolotova 2004;Zolotova & Ponyavin 2006, 2007Donner & Thiel 2007;Li 2008;Zolotova 2009Zolotova , 2010Li 2009;Li et al 2008Li et al , 2009cLi et al , 2010b. The N-S asymmetry of solar activity is related to the N-S phase difference of solar activity (Waldmeier 1957(Waldmeier , 1971Temmer, Veronig & Hanslmeier 2002;Temmer et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…By using cross-recurrence plot technique and wavelet transform method, Li (2008) found that the high-latitude solar activity (polar faculae) shows slight phase asynchrony between the northern and southern hemispheres. The N-S asynchrony of dynamical processes is an important topic for understanding the origin and evolution of active regions on the Sun and their various manifestations in the solar corona (Zolotova & Ponyavin 2006, 2007Zolotova 2009Zolotova , 2010.…”
Section: Introductionmentioning
confidence: 99%